Parathyroid Apoplexy Following Cinacalcet Treatment in Primary Hyperparathyroidism - Di Dalmazi, Giulia; Giuliani, Cesidio; Napolitano, Giorgio (Frontiers in Endocrinology, 2018)
Cinacalcet, a calcimimetic drug, is considered a safe and valid option for the treatment of hypercalcemia in patients with primary hyperparathyroidism who are unable to undergo parathyroidectomy. Hypocalcemia and gastrointestinal adverse reactions are the main side effects reported in patients treated with cinacalcet. We present here the case of an 80-years-old patient with primary hyperparathyroidism treated with cinacalcet for seventeen months who developed a severe and symptomatic episode of hypocalcemia requiring hospitalization one month after reaching a daily dose of 180 mg. Follow-up laboratory and imaging exams showed remission of primary hyperparathyroidism and disappearance of the parathyroid adenoma, leading us to postulate that cinacalcet therapy had caused a parathyroid infarction resulting in severe hypocalcemia with a normalization of the elevated serum parathyroid hormone levels. No known cases of iatrogenic parathyroid apoplexy have thus far been described. We report here the first case of parathyroid apoplexy due to the administration of cinacalcet in a patient with primary hyperparathyroidism. Parathyroid apoplexy features heterogeneous clinical manifestations ranging from relatively asymptomatic to potentially life-threatening cases. The occurrence of this complication should be carefully considered in patients with primary hyperparathyroidism in therapy with cinacalcet.